Hubungan motivasi, perilaku menjaga oral hygiene dan indeks plak siswa pengguna piranti ortodontik cekat di SMA se-Kecamatan Bangli - Luh Putu Widiastri; Putu Ika Anggaraeni; Desak Putu Yuli Kurniati (School of Dentistry Faculty of Medicine Udayana University, 2020)
Background: The success of orthodontic treatment depends on oral hygiene of the patient. Maintaining a good oral hygiene takes a lot of motivation and good behavior. There’s two motivations, intrinsic motivation and extrinsic motivation. A good motivation comes from inside (instrinsic motivation) not from outside (extrinsic motivation). Motivation influences a person's behavior to maintain oral hygiene, which is very influential on the success of fixed orthodontic treatment so it needs to be investigated. The aim of the study is to investigate the correlation between motivation to perform fixed orthodontic treatment, the behavior of maintaining oral hygiene and plaque index. Methods: This study was observational analytic cross-sectional. The 64 participants were students using fixed appliance from senior high school in Bangli District. A questionnaire was used to collect participant’s motivation and behavior. The plaque index was calculated using Modified Sillness-Loe. Result: Chi-square test show there’s significant correlation between instrinsic motivation and plaque index (p<0.05). No significant correlation between extrinsic motivation and plaque index (p>0.05). Significant correlation was found between maintaining oral hygiene behavior and plaque index (p<0.05). Conclusion: intrinsic motivation and behavior of maintaining oral hygiene can affect plaque index. Latar Belakang: Keberhasilan perawatan ortodontik cekat sangat dipengaruhi oleh oral hygiene dan kooperatif pasien. Pemeliharaan oral hygiene selama perawatan memerlukan motivasi yang kuat dan perilaku menjaga oral hygiene yang baik. Motivasi pasien melakukan perawatan ortodontik cekat terdiri dari dua motivasi yaitu motivasi intrinsik dan motivasi ekstrinsik. Motivasi yang baik berasal dari diri sendiri (intrinsik) bukan dari faktor lingkungan (ekstrinsik). Motivasi mempengaruhi perilaku seseorang menjaga oral hygiene, yang sangat berpengaruh terhadap keberhasilan perawatan ortodontik cekat sehingga perlu diteliti lebih lanjut. Tujuan dalam penelitian ini adalah untuk mengetahui hubungan motivasi melakukan perawatan ortodontik cekat, perilaku menjaga oral hygiene dan indeks plak. Metode: Penelitian ini adalah observasional analitik cross-sectional. Sampel sebanyak 64 siswa pengguna piranti ortodontik cekat di SMA se-Kecamatan Bangli. Data motivasi dan perilaku diperoleh menggunakan kuesioner dan data indeks plak melalui metode Modified Sillness-Loe. Hasil: Hasil analisis Chi-square menunjukkan ada hubungan yang signifikan antara motivasi intrinsik terhadap indeks plak (p<0,05). Tidak ada hubungan yang signifikan antara motivasi ekstrinsik dengan indek plak (p>0,05). Ada hubungan yang signifikan antara perilaku menjaga oral hygiene terhadap indeks plak (p<0,05). Kesimpulan: Motivasi intrinsik dan perilaku menjaga oral hygiene berpengaruh terhadap indeks plak.